The space of the catholicon of Hosios Loukas in Phocis and its possible prototype, the church of Sts. Sergius and Bacchus in Constantinople - Shcherbakova, Alexandra V. (Actual Problems of Theory and History of Art, 2012)
The architecture of the catholicon of Hosios Loukas monastery (attributed to the first half of the 11th century) is an octagon on squinches of a complicated plan with galleries. It is the most sophisticated and well-preserved example of this type of sacral building of the Middle-Byzantine period. This research addresses the origin of the architectural image of Hosios Loukas catholicon. The 6th с. church of Sts. Sergius and Bacchus in Constantinople could be considered as the most probable prototype in this case.
Keywords: Hosios Loukas; church of Sts. Sergius and Bacchus; Middle Byzantine architecture; Byzantine architecture; Byzantium; octagon on squinches; octagon; church; architecture of the 6th century; architecture of Justinian era